Pseudoxanthoma Elasticum: Report of Two Cases - Israel Antonio Esquivel-Pinto; Maria Elisa Vega-Memije; Araceli Alvarado-Delgadillo; Andres Eduardo Campuzano-Garcia; Amairani Manríquez-Robles (Karger Publishers, 2021)
Elastic pseudoxanthoma is a rare disease with autosomal recessive inheritance, also known as Grönblad-Strandberg syndrome, characterized by pathological mineralization of the elastic fibers in the connective tissue, affecting principally the dermis of skin, media, and intima of blood vessels and Bruch's membrane of the eye. The genetic defect of the disorder is located on chromosome 16p13.1 and disease is caused by the lack of functional ABCC6 protein, which in turn causes extracellular accumulation and deposition of calcium and other minerals in the elastic tissue. In this article we present two cases of this rare disease. We emphasize, in the diagnostic criteria, the importance of its early diagnosis and the current therapeutic approaches.